2006
DOI: 10.1039/b409898f
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in preparative enzymatic syntheses of carbohydrates

Abstract: This review covers advances and developments in the use of enzymes in synthetic mono- and oligosaccharide chemistry. Particular attention is paid to the use of aldolase/ketolases, glycosidases, glycosyltransferases, lipases, and coupled multi-enzyme biotransformations; 172 references are cited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 174 publications
(145 reference statements)
0
20
0
Order By: Relevance
“…The chemical and enzymatic syntheses of many natural, and modified, sugar-NDPs have received considerable attention because of the expanding use of glycosyltransferases as biocatalysts for preparative-scale biotransformations. [3,4] Conversely, the synthesis of hexose-derived sugar-NMPs has been less extensively addressed, and to our knowledge, the potential of native or engineered sialyltransferases as an alternative subset of biotransformation tools, beyond their use with CMP-sialic acid analogues, [5] remains unexplored. To be able to pursue such studies requires routine access to numerous sugar-NMP conjugates.…”
Section: Practical Synthesis Of Sugar Monophosphonucleotidesmentioning
confidence: 99%
“…The chemical and enzymatic syntheses of many natural, and modified, sugar-NDPs have received considerable attention because of the expanding use of glycosyltransferases as biocatalysts for preparative-scale biotransformations. [3,4] Conversely, the synthesis of hexose-derived sugar-NMPs has been less extensively addressed, and to our knowledge, the potential of native or engineered sialyltransferases as an alternative subset of biotransformation tools, beyond their use with CMP-sialic acid analogues, [5] remains unexplored. To be able to pursue such studies requires routine access to numerous sugar-NMP conjugates.…”
Section: Practical Synthesis Of Sugar Monophosphonucleotidesmentioning
confidence: 99%
“…[1][2][3][4][5] They find applications in research and development 1,2,6-8 and are widely used in industrial processes. 9,10 Glycosidases and glycosyltransferases find use in the synthesis of glycosides and oligosaccharides, whereas oxidoreductases, lyases, and ligases are basically applied to modify monosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Glycosidases and glycosyltransferases find use in the synthesis of glycosides and oligosaccharides, whereas oxidoreductases, lyases, and ligases are basically applied to modify monosaccharides. 1,2,11,12 Such broad range of applications implies a general interest to understand molecular foundations of these diverse catalytic processes. For that purpose, it is necessary to get a detailed knowledge of substrate recognition to understand enzymatic effectiveness and to study roles of enzymes in cellular identification procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, synthesis of the glycoconjugate by enzymatic transformation is used as an alternative method in manufacturing pharmaceuticals, fine chemicals, and food ingredients, due to the highly selective catalytic reactions, its environmental friendly nature, and mild reaction conditions of biotechnology. [8][9][10][11] It has been found that some enzymes are able to catalyze transglycosylation reactions to synthesize oligosaccharides or glycoconjugate molecules. [12][13][14][15][16] It is known that, Cyclodextrin-glycosyltransferase (CGTase EC 2.4.…”
Section: Introductionmentioning
confidence: 99%